(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2020)
The scope of this paper is to study, from a legal perspective, the recent figure of smart contracts, automatic software programs built on blockchain platforms. More specifically, it is studied how they may impact the contractual legal world, acting as the Law’s response to the challenges proposed by the society, that is permanently evolving. Basically, it will be investigated whether these contracts are, effectively, an innovative legal tool or not – an issue that, considering their incipient disposition, has not yet been resolved. It is expected to clarify the actual legal side of what is technically known as smart contracts, which will be referred, in the interface of law and technology, as smart legal contracts. Thus, it will be analyzed: (i) its legal framework; and (ii) its possible applications vis-à-vis the German legal world, particularly in the contractual aspect. This investigation is justified, above all, by the potential of the referred “contracts” of modifying the segment dynamics – among possible modifications, it can be mentioned, for instance, the simplification and automation of processes provided by its inherent self-execution mechanism.